INNOVATIVE EDUCATION AS A RESPONSE TO THE CHALLENGES OF INFORMATION REVOLUTIONS AND POTENTIAL OF SOCIAL TRANSIT - Zhuk, M.B.; Constanchak, С. (Journal of Information Technologies in Education (ITE), 2010)
An innovative model becomes a key factor of development in a context of globalization and information revolutions. Innovative education is a priority for this development. As for transforming countries transitive technologies create the significant potential of successful changes.